2009
DOI: 10.2337/db08-1361
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Stress Activates Inflammation and Reduces Glucose Metabolism by Suppressing AMP-Activated Protein Kinase in the Heart

Abstract: OBJECTIVEHeart failure is a major cause of mortality in diabetes and may be causally associated with altered metabolism. Recent reports indicate a role of inflammation in peripheral insulin resistance, but the impact of inflammation on cardiac metabolism is unknown. We investigated the effects of diet-induced obesity on cardiac inflammation and glucose metabolism in mice.RESEARCH DESIGN AND METHODSMale C57BL/6 mice were fed a high-fat diet (HFD) for 6 weeks, and heart samples were taken to measure insulin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 47 publications
9
111
1
1
Order By: Relevance
“…Consistent with our findings in these mice, nontransgenic models of lipid overload using long-term high-fat diet or streptozotocin treatment have also demonstrated increased numbers of macrophages within the hearts of insulin resistant and/or diabetic mice (13,30). However, assessing the influence of cardiac macrophages on LV function using cell depletion strategies with these models is confounded by the concomitant role of macrophages in promoting the primary dysregulation of systemic metabolism, which is further modified by macrophage depletion (16,21).…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with our findings in these mice, nontransgenic models of lipid overload using long-term high-fat diet or streptozotocin treatment have also demonstrated increased numbers of macrophages within the hearts of insulin resistant and/or diabetic mice (13,30). However, assessing the influence of cardiac macrophages on LV function using cell depletion strategies with these models is confounded by the concomitant role of macrophages in promoting the primary dysregulation of systemic metabolism, which is further modified by macrophage depletion (16,21).…”
Section: Discussionsupporting
confidence: 68%
“…These results indicate that exercise-specific effects possibly involving AMPK may be involved in the improvement of muscle glucose metabolism following exercise. Moreover, our recent study found activation of inflammatory response in the heart following HFDinduced obesity, and this was associated with cardiac insulin resistance (18). In the current study, high-fat feeding increased myocardial levels of MCP-1 and IFN␄, and weight loss following a LFD switch or exercise attenuated myocardial inflammation.…”
Section: E973 Weight Loss Improves Inflammation and Insulin Sensitivitysupporting
confidence: 50%
“…A horseradish peroxidase-conjugated secondary antibody (Bio-Rad) was used for staining at room temperature for 1 h. After being washed three times, metal enhanced 3,3-diaminobenzidine-tetrahydrochloride substrate was added to tissue and incubated for 15 min. Tissue was also counterstained with hematoxylin stain for 1 min, washed with ultrapure water, and mounted with mounting medium (Thermo Fisher Scientific, Waltham, MA) (18). Local levels of cytokines (IL-6, TNF␣, IL-1␀, IFN␄, and IL-10) and chemokine [macrophage chemoattractant protein (MCP-1)] in white adipose tissue, skeletal muscle, liver, and heart, as well as serum cytokines (IL-1␣, IL-5, IL-6, and IL-10), were measured using multiplexed Luminex.…”
Section: E966 Weight Loss Improves Inflammation and Insulin Sensitivitymentioning
confidence: 99%
“…The characteristics observed in both mouse and human models of diabetic cardiomyopathy, such as lipid accumulation, oxidative stress, mitochondrial dysfunction, and cardiomyocyte cell death, have been shown to trigger inflammation. [122][123][124][125] Cardiac inflammation and leukocyte recruitment, as observed in the setting of diabetic cardiomyopathy, seems to be mediated in part through the NLRP3 inflammasome in a similar fashion to MI. 68,[126][127][128][129][130] It has been hypothesized that the mechanism of inflammasome activation in diabetic cardiomyopathy is dependent on the combination of oxidative stress and reactive oxygen species production, as a result of mitochondrial dysfunction.…”
Section: Diabetic Cardiomyopathy and Chronic Inflammationmentioning
confidence: 99%